2012
DOI: 10.1007/s10461-012-0360-5
|View full text |Cite
|
Sign up to set email alerts
|

HIV Knowledge and Sexual Risk Behavior Among Pregnant Couples in South Africa: The PartnerPlus Project

Abstract: In sub-Saharan Africa, 60 % of people living with HIV are women and most are of childbearing age. Alarmingly, seroconversion rates during pregnancy are high and increase as pregnancy progresses, highlighting the importance of increasing HIV-knowledge among pregnant women and their partners. This study compared sexual risk behavior, HIV knowledge and condom use pre- to postpartum among South African couples (n = 239 couples) randomly assigned to an intervention or an enhanced standard of care with the PMTCT pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 26 publications
1
14
2
1
Order By: Relevance
“…In addition, health education should address misconceptions about the effects of antiretrovirals. In this study HIV knowledge was not found to be associated with HIV risk behaviour, unlike in a previous study in South Africa [39]. …”
Section: Discussioncontrasting
confidence: 95%
“…In addition, health education should address misconceptions about the effects of antiretrovirals. In this study HIV knowledge was not found to be associated with HIV risk behaviour, unlike in a previous study in South Africa [39]. …”
Section: Discussioncontrasting
confidence: 95%
“…Misconceptions around serodiscordance are well-documented in South Africa (83,84), and commonly lead to the practice of testing by proxy (85), which precludes opportunities to reduce sexual risk-taking that accompanies awareness of serodiscordant status (86). Other concerning knowledge gaps identified included that almost half of women reported that a woman is protected from HIV if her partner is circumcised.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research among high school students in Cape Town found that knowledge regarding how to use a condom and how STIs are transmitted directly predicted condom use at last sexual occasion (Eggers, Aaro, Bos, Mathews, & de Vries, 2013). Furthermore, Villar-Loubet et al (Villar-Loubet et al, 2013) found that HIV-related knowledge mediated the effects of an HIV intervention on consistent condom use. Such findings suggest that HIV knowledge may be an important predictor of sexual risk behavior in the South African context.…”
Section: Introductionmentioning
confidence: 99%